Author Correction: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.
Keywords: dept.phy; peer-reviewed